Swarms, Herds, and Peoples: Examinations of Interspecies Dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
Gale OneFile includes Swarms, Herds, and Peoples: Examinations of Interspecie by David A. Bello and C. Michele Thompson. Click to explore.
Keywords: dept.his

To Master the Boundless Sea: The U.s. Navy, the Marine Environment, and the Cartography of Empire - Smith, Jason W. (University of North Carolina Press, 2018)
"As the United States grew into an empire in the late nineteenth century, notions like 'sea power' derived not only from fleets, bases, and decisive battles, but also from a scientific effort to understand and master the ocean environment. Beginning in the early nineteenth century and concluding in the first years of the twentieth, Jason W. Smith tells the story of the rise of the U.S. Navy and the emergence of American ocean empire through its struggle to control nature. In vividly told sketches of exploration, naval officers, war, and, most significantly, the ocean environment, Smith draws together insights from environmental, maritime, military, and naval history, and the history of science and cartography, placing the U.S. Navy's scientific efforts within a broader cultural context"–
SCSU Faculty Scholar Award
Keywords: History; Naval; History; Cartography; Imperialism and science; United States; History; Nautical charts; SCSU Faculty Scholar Award; United States; United States. Navy; award_winner; dept.his; faculty_collection

Human Rights in the People's Republic of China - Wu, Yuan-li; Chang, Maria Hsia; Cooper, John F.; Gregor, A. James; Michael, Franz H.; Lee, Ta-ling (Routledge, 2018)
Keywords: 20th century; Human rights; 21st century; China; History; Human rights; dept.his; faculty_collection

Focus introduction: Swarms, herds, and peoples—examinations of interspecies dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
As its title suggests, this Focus draws our attention to the shift in perspective brought about by environmental history, compared to the more traditional approaches of history of science. Here human knowledge of and interaction with animals are understood as part of a historically variable system that encompasses both the human realm and its environment, a system in which the various components interact and shape each other dynamically.
Citation Key Alias: lens.org/130-110-172-036-255, pop00336 tex.type: [object Object]
Keywords: dept.his; peer-reviewed; ⛔ No DOI found

Welcoming ruin: The Civil Rights Act of 1875 - Friedlander, Alan; Gerber, Richard Allan (Brill, 2018)
Keywords: dept.his

Edification through the memory of sins - Chrissidis, Nikolaos A. (Canadian-american Slavic Studies, 2018)
The article explores the practical uses of Eastern Orthodox indulgences as certificates of absolution with a dual function (as mnemonic tools and as public certificates of good standing with the church) in the early modern period. © KONINKLIJKE BRILL NV, LEIDEN, 2018
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00325 tex.type: [object Object]
Keywords: Eastern Orthodox indulgences; Eastern Orthodox penitential practices; Mese katastasis ton psychon; Patriarch Dositheos of Jerusalem; Purgatory; Synchorochartia; dept.his; peer-reviewed

“Notorious abuse,” “traditious ignorance,” and “ambitious incroachment” in seventeenth-century Dutch, English, and French maps of North America - Petto, Christine M. (Cartographica: The International Journal for Geographic Information and Geovisualization, 2018)
In consideration of Richard Daniel’s alarmed discourse found in the text accompanying his map of the English empire in America (1679), one must investigate the supposedly offending French, English, and Dutch maps of the second half of the seventeenth century for North America and, in particular, the region of the Atlantic coastline and the rhetorical devices of possession found on or in these geographical works. In addition to looking at territorial boundaries, one should also make note of armorial bearings, ships with naval ensigns, toponyms and their placement on the territory, dedicatory cartouches, legends with geographical or historical information, native scenes, and symbols for settlement. In addition to attention to possible constraints on or from the map trade, one must consider the correspondence between colonial officials and their respective governments regarding boundaries, encroachment, sovereignty, or the need for maps with a particular focus on the North American coastline. This correspondence reflects the state’s point of view, which in turn was often manifested on maps and in geographical works. Interestingly intertwined with this outspoken sense of rightful possession were the contemporary claims from some quarters that the cartographic enterprise of the late seventeenth century now embraced an empirical approach, as well as the seemingly opposing thread of the economic realities of the print trade, which often used old copper plates with little to no cartographic revision, so that long after political, economic, or military actions resulted in an “adjustment” in possession, printed maps, atlases, and other geographical works still reflected earlier circumstances. © University of Toronto Press
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/051-706-928-277-117, pop00268 tex.type: [object Object]
Keywords: Cartography; Colonies; England; France; History; Netherlands; New England; New Netherland; North America; Seventeenth-century maps; The Netherlands; United Kingdom; colonialism; dept.his; economic history; empirical analysis; historical cartography; human settlement; peer-reviewed; seventeenth century; territorial dispute

War and Environment - Smith, Jason W. (The Routledge History of Global War and Society, 2018)
Scholars have offered at least four distinct but interrelated conceptual frameworks for examining the relationship between militaries and the natural world.
Keywords: dept.his

Hope in an ad: Teaching consumerism and idealized womanhood using 1920s advertisements - Carter-David, Siobhan (Advertising & Society Quarterly, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed

Computer systems: Digital design, fundamentals of computer architecture and assembly language - Elahi, Ata (Springer International Publishing, 2018)
This textbook covers digital design, fundamentals of computer architecture, and assembly language. The book starts by introducing basic number systems, character coding, basic knowledge in digital design, and components of a computer. The book goes on to discuss information representation in computing; Boolean algebra and logic gates; sequential logic; input/output; and CPU performance. The author also covers ARM architecture, ARM instructions and ARM assembly language which is used in a variety of devices such as cell phones, digital TV, automobiles, routers, and switches. The book contains a set of laboratory experiments related to digital design using Logisim software; in addition, each chapter features objectives, summaries, key terms, review questions and problems. The book is targeted to students majoring Computer Science, Information System and IT and follows the ACM/IEEE 2013 guidelines. • Comprehensive textbook covering digital design, computer architecture, and ARM architecture and assembly • Covers basic number system and coding, basic knowledge in digital design, and components of a computer • Features laboratory exercises in addition to objectives, summaries, key terms, review questions, and problems in each chapter
Citation Key Alias: elahiComputerSystemsDigital2017
Keywords: ARM architecture; ARM processors; Assembly language; Boolean algebra; Computation theory; Computer architecture; Digital designs; Digital devices; Digital television; Information representation; Laboratory exercise; Laboratory experiments; Number system; Numbering systems; Reviews; Sequential logic; Textbooks; dept.csc